Aboriginal bark paintings from the Cahill and Chaseling collections, National Museum of Victoria, Melbourne, Australia. - Museum of Fine Arts (Houston, Tex.); National Museum of Victoria (Houston, Tex. : Museum of Fine Arts, 1965)
Introduction by A. McCullock with notes on Kakadu art; Catalogue of bark paintings from Oenpelli, Yirrkala and Cape Don, collected by P. Cahill (cattle station owner and W. Chaseling (missionary)
Cover title: Aboriginal bark painitngs from Australia
Keywords: National Museum of Victoria; Art, Aboriginal Australian -- Exhibitions; Economic sectors - Agriculture and horticulture - Pastoral industry - Beef cattle; Gaagudju / Gagadju / Gagadyu people (N50) (NT SD53-01); Cultural heritage - Protection - Museums and keeping places - Collections and acquisitions; Art - Painting - Bark; Cape Don (West Arnhem Land NT SC52-16); Gunbalanya / Oenpelli (West Arnhem Land NT SD53-01); Yirrkala (East Arnhem Land SD53-04); Kakadu / Alligator Rivers area (NT SD53-01, SD53-05)